The oracles my Filipino grandparents in America - Poblete, Pati Navalta (Berkeley, Calif. Heyday Books, 2006)
As a young girl growing up in California, Pati Navalta Poblete is dismayed to find her American way of life interrupted when her four grandparents arrive from the Philippines. Turning her adolescence upside down, they inspire her to name them "the Oracles" for the unfamiliar--and often unsolicited--wisdom they bring. Poblete tells her story of generational strife and familial clash of values with tenderness and humor. In sharp and unforgettable glimpses we see the shadows of superstition, the force of religion, and the embrace of family--sometimes welcome, sometimes not. Only years later did she begin to understand how much she had needed the Oracles to bring her own.--From publisher description.
College Student
Keywords: Poblete, Pati Navalta -- Childhood and youth; Poblete, Pati Navalta -- Family; Filipino American families -- California -- San Francisco; Filipino Americans -- California -- San Francisco -- Biography; Intergenerational relations -- California -- San Francisco; Grandparents -- California -- San Francisco -- Biography; Immigrants -- California -- San Francisco -- Biography; Grandparents -- Philippines -- Biography; San Francisco (Calif.) -- Biography